2008
DOI: 10.1037/0278-7393.34.1.237
|View full text |Cite
|
Sign up to set email alerts
|

The intermixed-blocked effect in human perceptual learning is not the consequence of trial spacing.

Abstract: A robust finding in humans and animals is that intermixed exposure to 2 similar stimuli (AX/BX) results in better discriminability of those stimuli on test than does exposure to 2 equally similar stimuli in 2 separate blocks (CX_DX)--the intermixed-blocked effect. This intermixed-blocked effect may be an example of the superiority of spaced over massed practice; in the intermixed, but not the blocked exposure regime, each presentation of a given stimulus (e.g., AX) is separated from the next by the presentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
44
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 16 publications
7
44
3
Order By: Relevance
“…The interleaved practice group outperformed both the blocked practice group and the blocked-with-cartoons group on a transfer test involving identification of new paintings by the same artists. These findings support the discriminative-contrast hypothesis because (a) the interleaved practice group was the only group that was presented with paintings from the different artists consecutively and hence could more easily contrast the styles of the different painters, and (b) spacing was controlled for in the blocked-with-cartoons group (Kang & Pashler, 2012; see also Mitchell, Nash, & Hall, 2008).…”
Section: Theoretical Accounts For Interleaving Effectssupporting
confidence: 67%
“…The interleaved practice group outperformed both the blocked practice group and the blocked-with-cartoons group on a transfer test involving identification of new paintings by the same artists. These findings support the discriminative-contrast hypothesis because (a) the interleaved practice group was the only group that was presented with paintings from the different artists consecutively and hence could more easily contrast the styles of the different painters, and (b) spacing was controlled for in the blocked-with-cartoons group (Kang & Pashler, 2012; see also Mitchell, Nash, & Hall, 2008).…”
Section: Theoretical Accounts For Interleaving Effectssupporting
confidence: 67%
“…The result is that blocked pre-exposure produces better performance in discriminating between AX and BX than is obtained in the control condition, but alternated pre-exposure leads to better discrimination still. We believe this to be the first demonstration of such an effect by simulation, and it fits well with demonstrations of such an effect (e.g., Mitchell, Nash and Hall, 2008;Hall, Blair and Artigas, 2006). The mechanism here seems to be one that could explain the finding reported by Hall and Rodriguez (2009) characterized by Hall (2003Hall ( , 2009 as alternated pre-exposure leading to associative activation of the unique components of the stimuli, which allows for some restoration of the loss in salience to these components that would otherwise have occurred.…”
Section: Perceptual Learningsupporting
confidence: 67%
“…One line has been followed by animal learning researchers (e.g., Blair & Hall, 2003; Blair, Wilkinson, & Hall, 2004; Dwyer & Mackintosh, 2002; Mackintosh, Kaye, & Bennett, 1991; McLaren, Kaye, & Mackintosh, 1989; McLaren & Mackintosh, 2000; Mitchell, Nash, & Hall, 2008; Symonds, Hall, & Bailey, 2002); the other line has been followed by sensory psychophysicists. Animal learning researchers have indicated that to fully understand the behavioral rules of learning, it is necessary to clarify the role of perceptual learning as a component of learning.…”
mentioning
confidence: 99%